The Effectiveness of Schema-Based Parenting Training on Frustration Tolerance and Dysfunctional Attitudes in Mothers of Children with Autism Spectrum Disorder - Amini, Sahar; Asaseh, Maryam; Honarparvaran, Nazanin; Kashani Vahid, Leila (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of schema-based parenting training on frustration tolerance and dysfunctional attitudes among mothers of children with Autism Spectrum Disorder (ASD). Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of mothers of children with Autism Spectrum Disorder in Shiraz. Participants were selected through convenience sampling from two schools and were randomly assigned to either the experimental group or the control group. The experimental group received schema-based parenting training, while the control group received no intervention. The research instruments included the Frustration Discomfort Scale developed by Harrington (2005) and the Dysfunctional Attitude Scale developed by Weissman and Beck (1978). Data were analyzed using multivariate and univariate analyses of covariance (MANCOVA and ANCOVA). Findings: The results indicated that schema-based parenting training had a significant effect on improving frustration tolerance and reducing dysfunctional attitudes among mothers. The effect sizes demonstrated a strong impact of the intervention on the components of frustration tolerance and dysfunctional attitudes. Conclusion: Schema-based parenting training can be used as an effective intervention for promoting the mental health of mothers of children with Autism Spectrum Disorder.